Business Development Strategy of Beverage Powder Company - Mahasin, M. Zaenal; Hartoyo; Hasbullah, Rokhani (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Indonesia is currently experiencing the fourth wave of the coffee trend, characterized by a sharp increase in the market size of the coffee shop business. This growth is due to the ease of starting a coffee business and the emergence of digital businesses. Coffee trends have triggered an increase in domestic consumption of coffee and other drinks like chocolate and tea. The powdered beverage industry as a supporting ingredient for beverage shops has also increased with the rapid growth of modern drinks. In the last five years, this business has also increased following the growth of the ready-to-drink coffee business. Frezzo is one of the Small Medium Enterprises (SMEs) of powdered beverage that enters the medium industry category which is quite strong in the B-to-B segment. Meanwhile, Frezzo is experiencing idle capacity and achieving low market share in beverage industry. Purpose: The objective of the research is to focus on the challenges encountered by PT Frezzo. The challenges include optimizing production capacity and market share in the rapidly evolving beverage industry through analyzing both conditions, internal and external, that influence the business growth of Frezzo Powder. This research aims to develop priorities that strategic for Frezzo’s business advancement, as well. Design/methodology/approach: This research describes analytical tools used to solve the problems which include Business Model Canvas (BMC); Porter's Five Forces; Strength, Weakness, Opportunity, Threat (SWOT); Internal External Matrix (IE Matrix) and Quantitative Strategic Planning Matrix (QSPM). Findings/Result: The results of the analysis found that Frezzo had weaknesses in the retail sales aspect, lack of promotion and marketing network. The study concludes that there are priority strategies can be mapped into a new business model that should be applied rapidly. The priority strategies involve addition of new partnerships to cooperate with, such hotels, restaurants and cafes (horeca). Another priority is addition of Frezzo outlets and retailers in considerable towns. And then, new product differentiation in practical drinks, size variations, along with intense advertisement and promotions via Google, TikTok and YouTube. The last priority is addition of horeca sales representatives and procurement of fully automatic machines.Conclusion: To optimize production capacity and market share in the rapidly evolving beverage industry, company focus market penetration through infiltration of market comprises activities of promoting, discount or reduction of price, and comprehensive in distributing product. In this case, the activities of market penetration are conducted by extending avenues in reseller and Frezzo stores.Originality/value (State of the art): This research is useful for similar companies to provide an overview for business development by taking advantage of opportunities, level of competition and alternative strategies according to market segments and company characteristics. Keywords: beverage industry, beverage shops, priority strategies, Frezzo, business development